Comparative analysis for renal stereotactic body radiotherapy using Cyberknife, VMAT and proton therapy based treatment planning. (14th March 2018) - Baydoun, Atallah; Vapiwala, Neha; Ponsky, Lee E.; Awan, Musaddiq; Kassaee, Ali; Sutton, David; Podder, Tarun K.; Zhang, Yuxia; Dobbins, Donald; Muzic, Raymond F.; Traughber, Bryan; Machtay, Mitchell; et al.
Abstract: Purpose: We conducted this dosimetric analysis to evaluate the feasibility of a multi‐center stereotactic body radiation therapy (SBRT) trial for renal cell carcinoma (RCC) using different SBRT platforms. Materials/methods: The computed tomography (CT) simulation images of 10 patients with unilateral RCC previously treated on a Phase 1 trial at Institution 1 were anonymized and shared with Institution 2 after IRB approval. Treatment planning was generated through five different platforms aiming a total dose of 48 Gy in three fractions. These platforms included: Cyberknife and volumetric modulated arc therapy (VMAT) at institution 1, and Cyberknife, VMAT, and pencil beam scanning (PBS) Proton Therapy at institution 2. Dose constraints were based on the Phase 1 approved trial. Results: Compared to Cyberknife, VMAT and PBS plans provided overall an equivalent or superior coverage to the target volume, while limiting dose to the remaining kidney, contralateral kidney, liver, spinal cord, and bowel. Conclusion: This dosimetric study supports the feasibility of a multi‐center trial for renal SBRT using PBS, VMAT and Cyberknife.